Protein Modification Employing Non-Canonical Amino Acids to Prepare SUMOylation Detecting Bioconjugates - Alexander C. Williard; Hannah J. Switzer; Christina A. Howard; Rui Yin; Brent L. Russell; Ritwik Sanyal; Shaun Yu; Trinity M. Myers; Brian M. Flood; Oliver Kerscher; Douglas D. Young (Pharmaceutics, 2022)
Protein modification with non-canonical amino acids (ncAAs) represents a useful technology to afford homogenous samples of bioconjugates with site-specific modification. This technique can be directly applied to the detection of aberrant SUMOylation patterns, which are often indicative of disease states. Modified SUMO-trapping proteins, consisting of a catalytically inactive ULP1 fragment (UTAG) fused to the maltose-binding protein MBP, are useful reagents for the binding and labeling of SUMOylated proteins. Mutation of this UTAG fusion protein to facilitate amber suppression technologies for the genetic incorporation of ncAAs was assessed to provide a functional handle for modification. Ultimately, two sites in the maltose-binding protein (MBP) fusion were identified as ideal for incorporation and bioconjugation without perturbation to the SUMO-trapping ability of the UTAG protein. This functionality was then employed to label SUMOylated proteins in HeLa cells and demonstrate their enrichment in the nucleus. This modified UTAG-MBP-ncAA protein has far-reaching applications for both diagnostics and therapeutics.